A One-Pot Method for The Synthesis of Nanocellulose from Palm Oil Empty Bunches Using Fe-Cr Combination Catalyst - Irwan Hidayatulloh; Sudrajat Harris Abdulloh; Lidya Elizabeth (ASEAN Journal of Chemical Engineering, 2025)
Oil Palm Empty Fruit Bunches (OPEFB) are one of the byproducts of Crude Palm Oil (CPO) production. Due to its high cellulose content, OPEFB can be processed into nanocellulose, one of its applications. The objective of this study was to determine the procedure for synthesizing nanocellulose from OPEFB using the one-pot method with a combination of Fe and Cr catalysts, as well as the properties and effect of the catalyst composition on the nanocellulose synthesized from OPEFB. In this investigation, OPEFB was processed into nanocellulose in a single vessel. The delignification step was conducted at 90oC for 5 hours with 30%-w/v H2O2, and the acid hydrolysis phase was conducted at 75oC for 1 hour with an 8%-w H2SO4 solution and Fe(NO3)3.9H2O and Cr(NO3)3.9H2O catalysts. The independent variables were the catalyst composition (3-7%-w/w) and Fe/Cr catalyst weight ratio (0-1). Based on the results, the highest nanocellulose yield was 37%-w, obtained with a catalyst concentration of 5%-w/w with a 0:1 Fe-Cr catalyst ratio. At the same time, the smallest lignin content was 1.711%-wt. which was obtained with a catalyst concentration of 3%-w/w with a Fe-Cr catalyst ratio of 0.5:0.5. Statistical analysis obtained an optimum variable of one-pot method at a catalyst concentration of 3%-w/w with a Fe-Cr catalyst ratio of 0:1. Nanocellulose yield obtained of 30.146%-w and lignin content of 1.610%-w. Meanwhile, from the experimental results at a catalyst concentration of 3%-w/w and a catalyst ratio of Fe-Cr 0:1, a nanocellulose yield of 29.616%-w and a lignin content of 1.799%-w was obtained. Nanocellulose was characterized by PSA, FTIR, TEM, and XRD analyses.